Traversing the heart : journeys of the inter-religious imagination - Kearney, Richard.; Rizo-Patron, Eileen. (Studies in Religion and the Arts, 2010)
The key wager of Traversing the Heart - Journeys of the Inter-religious Imagination is that a spiritual imaginary operating at the level of metaphor, narrative, symbol and epiphany can traverse the borders of dogma and ideology and open genuine conversations between wisdom traditions. Like every hermeneutics of the heart, this journey begins to unfold in a concrete space and time: the interreligious conference at Bangalore in June 2007. While this collection does not claim to cover the religious traditions of all continents, its concluding essay on transculturation in Andean-Christian art highlights the importance of the North-South dialogue as a necessary supplement to the East-West one largely addressed in the book. As a call to future journeys and dialogue, this volume aims to communicate the one seminal lesson learned during the India conference: that in our third millennium, religions will be inter-religious or they will not be at peace.